Influence of gate and channel engineering on multigate MOSFETs-A review. (August 2017) - Ramesh, R.
Abstract: The design of CMOS circuits using nanoscale MOSFET has become very difficult nowadays as device modeling faces new challenges such as short channel effects and mobility degradation. Gate engineering and channel engineering reduces these challenges and improves the mobility of the carriers, resulting in improved characteristics such as drain current and transconductance. In this review paper, the effect of gate and channel engineering on the characteristics (both D.C and high frequency (a.c)) of multigate MOSFETs have been investigated and presented. Highlights: The review article is written using the research articles published from 2002 to 2017. Influence of Gate engineering & Channel engineering on both d.c. and a.c characteristics has been studied. Recent developments in gate & channel engineering is also included. The effect of gate misalignment effects in multigate MOSFETs are also analyzed.